Is trastuzumab as a single agent obsolete in early breast cancer? No. (February 2019) - Bianchini, Giampaolo
Abstract: Until very recently, the "one size fits all" approach, with trastuzumab and chemotherapy with or without endocrine therapy, has been considered standard of care in almost all patients with HER2-positive early breast cancer. The combination of trastuzumab and chemotherapy is considered an undeniable therapy in this setting, given the unquestionable clinical benefit and the favorable safety profile. This almost universal adoption of trastuzumab-based therapies in early breast cancer has led to a proportional increase of overtreated patients, thus making treatment de-escalation in HER2-positive early breast cancer one of the major and more urgent unmet clinical need. In patients with HER2-positive disease at low/intermediate risk, single agent trastuzumab is not at all obsolete, and actually it remains the standard of care and represents the basis for many current efforts to a tailored treatment de-escalation. In this population, it is now crucial to improve treatment tailoring, by fine-tuning both patient selection and treatment administration. Highlights: Trastuzumab and chemotherapy is considered an undeniable therapy in the setting of HER2-positive early breast cancer. This has led to a proportional increase of overtreated patients. Treatment de-escalation in HER2-positive early breast cancer is one of the major and more urgent unmet clinical need. In patients with HER2-positive disease at low/intermediate risk, single agent trastuzumab is still the standard of care. It is now crucial to improve treatment tailoring, by fine-tuning both patient selection and treatment administration.